Reflections on team culture, structure and function of an intensive support service centred on positive behavioural support. Issue 4 (3rd October 2016) - Patterson, Lawrence A.; Berry, Samuel
Abstract : Purpose: The purpose of this paper is to explore experiences of team culture, structure and function of an intensive support service (ISS) within the context of the recent service guidance "Building the Right Support" (NHS England, Local Government Association and Association of Directors of Adult Social Services, 2015). Reflections on the Hampshire and Southampton ISS set up in 2010 are discussed with a view to informing a debate about frameworks for ISS services nationally. Design/methodology/approach: A reflective piece, drawing on experience and case examples. Findings: This paper describes that a key function of an ISS is making individuals safe and this is significantly assisted by using shared team formulation, which can enable information and perspectives to be shared between and within teams as rapidly as possible. Further, a case is made for recognising the importance of inter-disciplinary practice, as the Southampton and Hampshire ISS has removed the "old fashioned" demarcations that led to individuals seeing a "procession" of different professionals from different disciplines. This relates to team structure, but importantly is about a culture of holding a shared identity based on positive behavioural support values, rather than a traditional uni-disciplinary perspective. Practical implications: ISS models are being proposed by NHS England and this paper suggests some important practical aspects. Originality/value: Limited literature exists examining the team culture within ISSs, which contributes to desired outcomes for service users. This paper opens a debate about structural and functional aspects of service delivery in this service model.